Effects of mandibular advancement surgery on the temporomandibular joint and muscular and articular adaptive changes—a systematic review. Issue 5 (May 2016) - Bermell-Baviera, A.; Bellot-Arcís, C.; Montiel-Company, J.M.; Almerich-Silla, J.M.
Abstract: The objective of this study was to assess the anatomical changes to the condyle and articular disc following mandibular advancement surgery, the adaptation of the masticatory muscles, and the improvement or worsening of temporomandibular disorders (TMD) in patients with pre-existing disorders and those who developed them following surgery. Four databases were searched systematically: PubMed, Scopus, Embase, and Cochrane Library. Of the 544 articles initially selected, 219 were duplicates and a further 165 were excluded on the basis of their titles and abstracts. On reading the full text, 89 were excluded because they were of no interest and 43 because they did not meet the inclusion criteria. Of the remaining 28 articles, six were excluded because they were considered of low quality and 22 articles were reviewed. Mandibular advancement surgery with condyle repositioning is associated with less TMD. Condylar resorption is a physiological process with a multifactorial aetiology. It is accelerated following mandibular advancement surgery but is not a contraindication to this procedure. Despite the large number of studies on the effects of mandibular advancement surgery on the temporomandibular joint (TMJ), this surgery can neither be said to improve nor to worsen TMJ health.